(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the insecticide susceptibility and ULV spray efficacy of insecticides against Ae. aegypti and Ae. albopictus mosquitoes at several sites in the Southern region of Vietnam. Research method: Controlled experiment Results: Ae. aegypti mosquitoes showed 2/4 sites resistance and 2/4 sites increased tolerance to Deltamethrin 0.05%; 4/5 sites resistance and 1/5 sites sensitivity to Alphacypermethrin 0.08%; 3/3 sites resistance to Permethrin 0.75%; and 2/2 sites sensitivity to Malathion 5%. Ae. albopictus mosquitoes showed 2/2 sites resistance to Deltamethrin 0.05%; 1/1 sites sensitivity to Alphacypermethrin 0.08%; and 1/1 sites resistance to Permethrin 0.75%. ULV spray efficacy of insecticides against Ae. aegypti mosquitoes was 6/7 sites, 1/7 sites not; against Ae. aegypti mosquitoes, 2/2 sites were achieved. Conclusion: Aedes aegypti and Aedes albopictus (F1) mosquitoes hatched from larvae collected at the study sites were resistant to Deltamethrin 0.05%, Alphacypermethrin 0.08%, Permethrin 0.75%, but remained sensitive to Malathion 5%; the chemicals used in the dengue fever control program in the provinces still have good efficacy.